Liberalism : A Counter-History - Losurdo, Domenico (London Verso, 2014)
"In this definitive historical investigation, Italian author and philosopher Domenico Losurdo argues that from the outset liberalism, as a philosophical position and ideology, has been bound up with the most illiberal of policies: slavery, colonialism, genocide, racism and snobbery. Narrating an intellectual history running from the eighteenth through to the twentieth centuries, Losurdo examines the thought of preeminent liberal writers such as Locke, Burke, Tocqueville, Constant, Bentham, and Sieyès, revealing the inner contradictions of an intellectual position that has exercised a formative influence on today's politics. Among the dominant strains of liberalism, he discerns the counter-currents of more radical positions, lost in the constitution of the modern world order"--
Include Index and References
Keywords: Liberalism -- Political science -- POLITICAL SCIENCE -- Political Ideologies -- Conservatism & Liberalism